Erratum: Compensating and equivalence properties of optical waveguides with a linear and sinusoidal variation of the core refractive index and core size along the propagation direction (Microwave Opt Technol Lett (2003) 39 (348)) - Pandey P.C.; Ojha S.P. (My University, 2025)
[No abstract available]